2014
DOI: 10.1002/jbm.b.33199
|View full text |Cite
|
Sign up to set email alerts
|

Extended fatigue life of a catalyst free self‐healing acrylic bone cement using microencapsulated 2‐octyl cyanoacrylate

Abstract: The tissue adhesive 2-octyl cyanoacrylate (OCA) was encapsulated in polyurethane microshells and incorporated into bone cement to form a catalyst free, self-healing bone cement comprised of all clinically approved components. The bending strength, modulus, and fatigue lifetime were investigated in accordance with ASTM and ISO standards for the testing of PMMA bone cement. The bending strength of bone cement specimens decreased with increasing wt% capsules content for capsules without or with OCA, with specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Incorporation of the 2-octyl cyanoacrylate slowed down progressive crack propagation under loading compared with unreinforced PMMA cement. In subsequent work [24], it was shown that reinforced specimens were able to withstand twice as many repetitive loading cycles before failure compared with unreinforced specimens. Cyanoacrylate films with a broad range of nanostructured architectures were also created [25].…”
Section: Notable Advances In Cyanoacrylate Adhesivesmentioning
confidence: 99%
“…Incorporation of the 2-octyl cyanoacrylate slowed down progressive crack propagation under loading compared with unreinforced PMMA cement. In subsequent work [24], it was shown that reinforced specimens were able to withstand twice as many repetitive loading cycles before failure compared with unreinforced specimens. Cyanoacrylate films with a broad range of nanostructured architectures were also created [25].…”
Section: Notable Advances In Cyanoacrylate Adhesivesmentioning
confidence: 99%
“…Biocompatibility is essential for self-healing systems used in biomedical applications; if the system is effective in healing a crack but toxic, it is futile in these applications. Self-healing materials formulations proposed for a biomedical application must pass both ASTM and ISO standards for mechanical and biocompatibility characterization of the materials (Brochu, Matthys, Craig, & Reichert, 2015). Standard protocols are yet to be established for the quantification of the self-healing capacity of biomaterials (Diba et al, 2018).…”
Section: Nanoscale Capsule Technologies For Improved Performancementioning
confidence: 99%
“…In this approach, the self‐healing polymerization does not rely on chemical reactions or external stimuli, and the capsules can be added as an independent component of the bone cement formulation. Brochu et al (2015) also fabricated a capsule‐based self‐healing system using only materials that are currently in clinical use. This system encapsulated the water reactive healing agent, 2‐octul‐cyanoacrylate (OCA) tissue adhesive, in PU microcapsules.…”
Section: Capsule Based Self‐healing Systemsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10]. The working principle of this autonomic healing strategy depends upon an adequate release of the capsule content whenever the matrix is internally damaged.…”
Section: Introductionmentioning
confidence: 99%